2016
DOI: 10.1523/jneurosci.3919-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

The Proinflammatory Cytokine Interleukin 18 Regulates Feeding by Acting on the Bed Nucleus of the Stria Terminalis

Abstract: The proinflammatory cytokine IL-18 has central anorexigenic effects and was proposed to contribute to loss of appetite observed during sickness. Here we tested in the mouse the hypothesis that IL-18 can decrease food intake by acting on neurons of the bed nucleus of the stria terminalis (BST), a component of extended amygdala recently shown to influence feeding via its projections to the lateral hypothalamus (LH). We found that both subunits of the heterodimeric IL-18 receptor are highly expressed in the BST a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 67 publications
1
21
0
Order By: Relevance
“…The pattern of changes recorded in the hypothalamus was consistent with the pattern expected when animals experience a reduction in appetite. These effects were abolished in brain slices from the IL-18 knock-out mouse (Francesconi et al, 2016).…”
Section: Dual-intervention Point Model and 'Drifty Gene' Hypothesismentioning
confidence: 95%
See 1 more Smart Citation
“…The pattern of changes recorded in the hypothalamus was consistent with the pattern expected when animals experience a reduction in appetite. These effects were abolished in brain slices from the IL-18 knock-out mouse (Francesconi et al, 2016).…”
Section: Dual-intervention Point Model and 'Drifty Gene' Hypothesismentioning
confidence: 95%
“…Injection of IL-18 directly into this area of the brain in mice resulted in a significant reduction in food intake, but interestingly had no impact on physical activity levels, body temperature or energy expenditure (Francesconi et al, 2016). Brain slice work showed that neurons in the BST that project to the hypothalamus were strongly activated by glutamate, but that this excitatory effect was reduced when they were treated with IL-18.…”
Section: Dual-intervention Point Model and 'Drifty Gene' Hypothesismentioning
confidence: 99%
“…Energy expenditure was determined by using a computer-controlled open-circuit system (Oxymax System) that is part of an integrated Comprehensive Lab Animal Monitoring System (Columbus Instruments), as previously described (54).…”
Section: Methodsmentioning
confidence: 99%
“…There is recent evidence to suggest this may be the case. A recent study by Francesconi et al (33) reported that IL-18 reduces food intake by actions in the bed nucleus of the stria terminalis. The authors concluded that this is mediated via IL-18Ra, as these effects were not observed in IL-18Ra 2/2 mice.…”
Section: Discussionmentioning
confidence: 99%